2009
DOI: 10.2174/157340809787314247
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Carcinogensis and Suppression of Tumor Development by Inhibition of Enzymes and Molecular Targets

Abstract: Colorectal cancer (CRC) is the fourth most common cancer in the world. If detected at an early stage, treatment often might lead to cure. Of course prevention is better than cure. Epidemiological studies reveal that having a healthy diet often protects from CRC development. An important consideration in evaluating new drugs and devices is determining whether a product can effectively treat a targeted disease. There are a number of agents making their way into clinical trials by estimating their effects on biom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 248 publications
(264 reference statements)
0
26
0
Order By: Relevance
“…Previous studies have indicated that such activity may be mediated via the potential of polyphenols and their metabolites to induce cell cycle blockage in the G2/M phase in adenocarcinoma cells, perhaps through their effects on COX-2 activity (Shan, Wang, & Li, 2009;Yasui, Kim, Oyama, & Tanaka, 2009). On the other hand, these antiproliferative effects may be mediated, in part, by their direct cytotoxic action (Gómez-Alonso et al, 2012).…”
Section: Effect On Cell Proliferationmentioning
confidence: 99%
“…Previous studies have indicated that such activity may be mediated via the potential of polyphenols and their metabolites to induce cell cycle blockage in the G2/M phase in adenocarcinoma cells, perhaps through their effects on COX-2 activity (Shan, Wang, & Li, 2009;Yasui, Kim, Oyama, & Tanaka, 2009). On the other hand, these antiproliferative effects may be mediated, in part, by their direct cytotoxic action (Gómez-Alonso et al, 2012).…”
Section: Effect On Cell Proliferationmentioning
confidence: 99%
“…These biological activities include antioxidative (13,14), antiinflammatory, antiviral (15), and antihistamic (16) activities. These same biological activities have been observed in other promising cancer chemopreventive agents (17)(18)(19)(20). The effects of tricin on oncogenesis have been investigated by Gescher et al Their studies have shown that tricin suppresses the growth of human malignant breast tumor in nude mice (21).…”
mentioning
confidence: 61%
“…The AOM-induced ACF assays have been extensively used as an endpoint in short-term carcinogenesis and chemoprevention studies 11,12 . In previous reports we demonstrated the association of AOM and the occurrence of ACF in a rat model.…”
Section: Discussionmentioning
confidence: 99%